Peningkatan Penjualan UMKM Kopi Keliling Melalui Penerapan Digital Marketing Di Kabupten Pamekasan - Habbibur Rohim; Moh Norkholis; Umar Faruk; Achmarul Fajar; Fadali Rahman (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the impact of digital marketing implementation on the sales growth of mobile coffee MSMEs in Pamekasan Regency. The research method used is qualitative with a case study approach on three mobile coffee MSMEs that have implemented marketing through social media such as WhatsApp and Instagram. Data collection techniques were carried out through interviews, observations, and documentation. The results of the study indicate that the implementation of digital marketing has successfully increased consumer reach, expanded the market, and raised average sales by 35% within three months. In conclusion, digital marketing strategies are effective and relevant for mobile coffee MSMEs to improve competitiveness and sales revenue.